Mixed methods research teams: leveraging integrative teamwork for addressing complex problems - Poth, Cheryl; Georgiou, George; Mack, Emily; Kierstead, Matthew (Frontiers in Education, 2024)
Mixed methods research teams have garnered increased attention for their leveraging of diverse disciplinary and methodological expertise in pursuit of complex problems. We advance our theoretical viewpoint of integrative mixed methods research teamwork as necessary with empirical evidence demonstrating the equipping mixed methods researchers to study complex problems involving interacting systems and lacking known solutions. Integrative mixed methods research teamwork is distinguishable by the purposeful integration of qualitative and quantitative perspectives to generate novel outcomes that are greater than the sum of individual members’ contributions. Among the key dilemmas faced by mixed methods researchers wanting to work integratively within a team is the lack of practical guidance for how to get started, how to recognize the emergence of synergistic outcomes, and how to sustain a team’s integrative work. To begin addressing this gap, we describe three practical insights gleaned from examining our team interactions and outcomes using a reflection-in-action process during a recent empirical mixed methods case study of literacy practices. In our examination, we test the practical usefulness of a theoretical framework for demystifying the development of a mixed methods research team’s integrative capacity. Our insights contribute to refining teamwork practices by identifying enablers of integrative capacity and proposing ways to overcome hindrances that have not been previously elucidated. We argue that the capacity for integrative teamwork is essential for researchers employing mixed methods, allowing them to leverage inherent synergies when addressing complex problems.